2013
DOI: 10.12928/si.v11i2.1659
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Perancangan Skateboard Dengan Quality Function Deployment – House of Quality

Abstract: ABSTRAK Makalah ini membahas penentuan Customer I.PENDAHULUAN Skateboard adalah salah satu keluarga besar dari olahraga ekstrim di dunia. Skateboard pertama kali ditemukan dipertengahan tahun 1950, seiring dengan berkembangnya era surfing di daerah California, Amerika Serikat. Dalam beberapa catatan, permainan ini juga populer digolongkan dalam extreme sport. Alasannya adalah faktor bahaya yang dapat ditimbulkan. Semakin sulit rintangan/ track, maka semakin menantang untuk ditaklukkan. Hal tersebut akan lebih … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Hauser (1988) was explained the process of House of Quality started with Customer Requirement, Planning Matrix, Technical Response, Relationship Matrix, Technical Correlation, and then Target Matrix. The study of Kurniasih (2013) showed consumers' needs and desires for products from using the house of quality. Purwati et al (2017), in the study of Total quality service analysis, shows 29 attributes of customer needs and wants and 31 technical requirements formulated to meet customer wants and expectations.…”
Section: Methodsmentioning
confidence: 99%
“…Hauser (1988) was explained the process of House of Quality started with Customer Requirement, Planning Matrix, Technical Response, Relationship Matrix, Technical Correlation, and then Target Matrix. The study of Kurniasih (2013) showed consumers' needs and desires for products from using the house of quality. Purwati et al (2017), in the study of Total quality service analysis, shows 29 attributes of customer needs and wants and 31 technical requirements formulated to meet customer wants and expectations.…”
Section: Methodsmentioning
confidence: 99%
“…House of Quality merupakan tools pendukung proses identifikasi produk sehingga menjadi sebuah rancangan. HoQ juga mendefinisikan kebutuhan dan harapan customer dan bagaimana memenuhinya [10].…”
Section: House Of Quality (Hoq)unclassified
“…(Muryono, Irwansyah, and Budiyantara 2020). Pengolahan data dilakukan untuk mengetahui faktorfaktor yang dianggap penting dan perlu diperhatikan untuk meningkatkan kualitas jasa pelayanan kesehatan pada RSDC Wisma Atlet DKI Jakarta untuk pasien COVID-19 (Kurniasih 2013).…”
Section: Hasil Dan Pembahasanunclassified